The influence of socioeconomic characteristics and family support on the quality of life and well-being of the elderly in Jambi Province, Indonesia - Hardiani, Hardiani; Prihanto, Purwaka Hari; Junaidi, Junaidi (International Journal of Social Sciences and Management, 2019)
This study aims to analyze: 1) family support for the elderly in Jambi Province; 2) the quality of life and subjective well-being of the elderly; 3) the influence of socio-economic factors and family support on the quality of life and welfare of the elderly in Jambi Province.The data used is primary data based on interviews with selected elderly respondents. Family support, quality of life and subjective well-being of the elderly were measured quantitatively using a Likert scale and they were analyzed descriptively. The influence of socioeconomic factors and family support on the quality of life and welfare of the elderly were analyzed using structural equation modeling partial least square (SEM-PLS). The study found that: 1) Family support for elderly people in Jambi Province is relatively good. The dominant type of support is appreciation/recognition support while the lowest support is financial support; 2) The quality of life of the elderly in Jambi Province is relatively good. Social relationships quality has the highest quality score, while psychological quality has the lowest quality score; 3) Socio-economic characteristics of elderly families and the characteristics of elderly individuals have a significant effect on family support for the elderly. The quality of life of the elderly is directly influenced by family support. Furthermore, the elderly welfare is directly influenced by the quality of life of the elderly, family support and dan characteristics of elderly individuals. Int. J. Soc. Sc. Manage. Vol. 6, Issue-3: 63-74